DNA Methylation Signature of Epileptic Encephalopathy-Related Pathogenic Genes Encoding Ion Channels in Temporal Lobe Epilepsy - Tao, Hua; Chen, Zengqiang; Wu, Jianhao; Chen, Jun; Chen, Yusen; Fu, Jiawu; Sun, Chaowen; Zhou, Haihong; Zhong, Wangtao; Zhou, Xu; Li, Keshen (Frontiers in Neurology, 2021)
Epilepsy is characterized by highly abnormal synchronous discharge of brain neurons, and ion channels are fundamental in the generation and modulation of neural excitability. Considering that abnormal methylation can either activate or repress genes, this study was designed to explore the DNA methylation signature of pathogenic genes encoding ion channels in temporal lobe epilepsy (TLE). In total, 38 TLE patients and 38 healthy controls were enrolled in the study, and genomic DNA and total protein of the lymphocytes were extracted from peripheral blood samples to assess methylation and protein levels. The DNA methylation levels of all 12 genes examined were significantly lower in the TLE group than in the control group. After false-positive correction, 83.3% (10/12) of these genes, namely, gamma-aminobutyric acid type A receptor subunit beta1 (GABRB1), gamma-aminobutyric acid type A receptor subunit beta2 (GABRB2), gamma-aminobutyric acid type A receptor subunit beta1 (GABRB3), glutamate ionotropic receptor NMDA type subunit 1 (GRIN1), glutamate ionotropic receptor NMDA type subunit 2A (GRIN2A), glutamate ionotropic receptor NMDA type subunit 2B (GRIN2B), hyperpolarization activated cyclic nucleotide gated potassium channel 1 (HCN1), potassium voltage-gated channel subfamily A member 2 (KCNA2), potassium voltage-gated channel subfamily B member 1 (KCNB1), and potassium sodium-activated channel subfamily T member 1 (KCNT1), were still differentially expressed. Among these ion channels, HCN1 and KCNA2 were selected to evaluate the effects of DNA methylation, and the levels of these proteins were inversely upregulated in the TLE group compared to the control group. As the genes identified as having differential methylation levels are involved in both excitatory and inhibitory ion channels, this study observed by binary logistic regression that hypermethylated GARAB1 was an independent risk factor for TLE, indicating that the overwhelming effect of ion channels on TLE is probably inhibitory from the perspective of DNA methylation. All these findings support the involvement of DNA methylation in TLE pathologies, but the mechanisms need to be further investigated.